problem about function and relation mappimg

a function g from a set X to itself satisfies g^m=g^n for positive integers m and n with m>n.Here g^n stands for gogogo.......og(n times).Show that g is one one function iff g is onto function.

Note by Sayan Chaudhuri
8 years, 4 months ago

No vote yet
4 votes

  Easy Math Editor

This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.

When posting on Brilliant:

  • Use the emojis to react to an explanation, whether you're congratulating a job well done , or just really confused .
  • Ask specific questions about the challenge or the steps in somebody's explanation. Well-posed questions can add a lot to the discussion, but posting "I don't understand!" doesn't help anyone.
  • Try to contribute something new to the discussion, whether it is an extension, generalization or other idea related to the challenge.
  • Stay on topic — we're all here to learn more about math and science, not to hear about your favorite get-rich-quick scheme or current world events.

MarkdownAppears as
*italics* or _italics_ italics
**bold** or __bold__ bold

- bulleted
- list

  • bulleted
  • list

1. numbered
2. list

  1. numbered
  2. list
Note: you must add a full line of space before and after lists for them to show up correctly
paragraph 1

paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)example link
> This is a quote
This is a quote
    # I indented these lines
    # 4 spaces, and now they show
    # up as a code block.

    print "hello world"
# I indented these lines
# 4 spaces, and now they show
# up as a code block.

print "hello world"
MathAppears as
Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.
2 \times 3 2×3 2 \times 3
2^{34} 234 2^{34}
a_{i-1} ai1 a_{i-1}
\frac{2}{3} 23 \frac{2}{3}
\sqrt{2} 2 \sqrt{2}
\sum_{i=1}^3 i=13 \sum_{i=1}^3
\sin \theta sinθ \sin \theta
\boxed{123} 123 \boxed{123}

Comments

which book is this excerpt from?

Soham Chanda - 8 years, 4 months ago

may I present a solution?

1)If g is one-to-one then:

g(m)=g(n)g(mn)(x)=xg^{(m)}=g^{(n)}\Rightarrow{g^{(m-n)}(x)=x} and for some x0Xx_{0}\in{Χ}

g(mn)(x0)=x0g^{(m-n)}(x_{0})=x_{0}

if we set g(mn1)(x0)=ag^{(m-n-1)}(x_{0})=a then g(a)=x0g(a)=x_{0} which implies that for every x0X,a:g(a)=x0x_{0}\in{X},\exists{a}: g(a)=x_{0}, which is the definition of a surjective function.

2)If g is onto, and we set g(n)(x0)=cg^{(n)}(x_{0})=c for some x0x_{0} then, for all c, we have that g(mn)(c)=cg^{(m-n)}(c)=c.What we don't know yet is whether an x0x_{0} can be assigned to every value of c. But we can easily prove that if g is onto, g(n)g^{(n)} is onto. Now we can conclude that

g(x1)=g(x2)g(mn)(x1)=g(mn)(x2)x1=x2g(x_{1})=g(x_{2})\Rightarrow{g^{(m-n)}(x_{1})=g^{(m-n)}(x_{2})}\Rightarrow{x_{1}=x_{2}} which is valid for every x1,x2Xx_{1},x_{2}\in{X} as we proved above, so g is 1-1.

Kyriakos Grammatikos - 8 years, 4 months ago
×

Problem Loading...

Note Loading...

Set Loading...